Dialek dan Campur Kode Ujaran Bahasa Masyarakat Desa Pulau Belimbing Kabupaten Kampar - Rahayu, Ariyanti; Pilpa Sari, Yulna; Sinaga, Mangatur (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The main human communication tool is language which is used as an exchange of information between people, be it arguments, ideas or feelings. The use of language in people's daily lives can affect articulation in communicating and interacting between humans. Diversity in language creates its own uniqueness in communicating. The use of the language of the people in the tourist village of Belimbing Island is greatly influenced by the environment. This is what causes the mixed dialect used by the Belimbing Island villagers to be very unique and diverse. The purpose of this research is to know and study the diversity of languages ​​used by the people in the tourist village of Belimbing Island and to describe the Dialect and Code Mixing of the speech of the people in Wista Village, Belimbing Island. The method used is descriptive qualitative and sociolinguistic approach. The results of the study indicate the use of dialect and code mixing in communication carried out by the people in the tourist village of Belimbing Island.